Electrospray ionization mass spectrometric studies on uranyl complex with α‐hydroxyisobutyric acid in water–methanol medium. (17th April 2013) - Jaison, P. G.; Kumar, Pranaw; Telmore, Vijay M.; Aggarwal, Suresh K.
<x xml:space="preserve">Abstract</x> RATIONALE Hydroxycarboxylic acids are extensively used as chelating agents in the liquid chromatographic separation of actinides and lanthanides. They are also used as model compounds to understand the binding characteristics of humic substances. A systematic study of the speciation of uranyl‐α‐hyydroxyisobutyric acid (HIBA) in water–methanol is essential, as it is important to understand the various mechanisms responsible for the separation of these species in liquid chromatography. METHODS ESI‐MS studies were carried out using a tandem quadrupole‐time‐of‐flight mass spectrometer in positive and negative ion mode. The effects of solution composition, solute concentration and supporting electrolyte concentration on the ESI‐MS behavior of the uranyl species were studied. Transmission parameters such as the quadrupole ion energy and collision cell energy were optimized for acquiring the spectra of uranyl‐HIBA species, ensuring that the spectra reflect the solution equilibrium conditions. RESULTS The solution composition and concentration of the uranyl salt were found to influence the major uncomplexed uranyl species. Although the ESI parameters did not influence the species distribution of uranyl‐HIBA, the transmission parameters did have a significant effect. The overall trend in the complexation reaction between uranyl and HIBA was studied as a function of ligand‐to‐metal ratio. The species distribution obtained in positive ion mode was similar to that obtained in negative ion mode. CONCLUSIONS The study presents the optimization of the mobile phase conditions and the ESI‐MS parameters for the speciation of the uranyl‐HIBA system. The methodology was applied to obtaining the distribution of complexed and uncomplexed uranyl species for monitoring the trend in the complexation reaction. Copyright © 2013 John Wiley & Sons, Ltd.